Influence of Brand Image on Brand Loyalty Using Brand Trust and Social Media Engagement - Mandasari, Nur Fitriayu; Ashdaq, Muhammad; Radjab, Enny; Nadir, Muhammad; Mulatsih, Listiana Sri (Jurnal Aplikasi Manajemen, 2024)
Several variables influencing student loyalty formation include brand image, trust, and social media engagement. This research aims to understand brand loyalty within private universities in West Sulawesi Province, Indonesia. The study focuses on the influence of brand image and investigates the mediating roles of brand trust and social media engagement in shaping brand loyalty among students and alumni. The sample size of 148 respondents, including active students and non-graduating alums from public universities, was chosen to capture a diverse perspective on brand loyalty in higher education. The research method employed was Structural Equation Modeling (SEM), and the data was gathered from official social media accounts managed by four regional private universities. The aim was to provide a rigorous and comprehensive analysis. The results of this study indicate that the brand image of private tertiary institutions has a positive effect on brand trust, the brand image does not affect loyalty, brand image has a positive impact on social media engagement, brand trust has no effect on brand loyalty, social media engagement has no impact on brand loyalty, and there is no direct relationship between brand image loyalty through the variable brand trust and social media engagement and social media engagement. Brand image, trust, and social media engagement do not affect student loyalty. The company's managers strive through social media to provide information that consumers need anytime and anywhere, in addition to providing services related to advice and physical services offered on bicycle products through particular messages on social media.